Intelligent terminal identification technology toward 6G - Shida XIA; Jin XU; Xiaofeng TAO (物联网学报)
The intelligent terminal will greatly expand the applications of 6G .However,it will also make 6G face with greater security threats.The reliable terminal identification technology is the premise to ensure the security of 6G networks.Firstly,based on the network architecture and terminal characteristics,the requirements and challenges of 6G intelligent terminal identification were summarized.Then,the development trend was put forward for 6G intelligent terminal identification.Finally,physical layer authentication was explored to achieve possible realization of intelligent terminal identity authentication mechanism in 6G networks.